(untitled) (Applied Biological Research, 2022)
The unprecedent challenges in the treatment of infectious diseases caused by the alarming increase of multidrug resistant bacteria are serious concern worldwide. The present study focused on evaluating the antibacterial activity of methanolic extract of cardamom (Elettaria cardamomum) pods; and in finding out the minimum inhibitory concentrations (MICs) against Klebsiella pneumoniae strain MDR and Staphylococcus aureus. The pod extract was also screened for antioxidant activity. The extract at the concentrations of 500 and 1000 mg mL-1showed higher zones of growth inhibition against K. pneumoniaand S. aureus. MICs of K. pneumoniae and ± 0.01% of reducing power) at the concentration of 1000 µg extract. The study that the methanolic pod extract of cardamom pods have significant antibacterial potential against MDR pathogens and can be develped astreatment for MDR infections.